Spatial and seasonal variations of elemental and ion components in air particulate matters in three mega-cities in China. Issue 1 (2nd January 2019) - Lv, Jungang; Liu, Shuo; Li, Yuanyuan
Abstract: Beijing–Tianjin–Hebei region is one of the most important political, economic and cultural centers of China. The rapid development of economy in last decades has caused severe air pollution problems, which has resulted in considerable harm to local ecological environment and human health. In this study, total 671 air samples were collected from Beijing, Tianjin and Shijiazhuang (the capital city in Hebei province), one reference site and four background sites in four seasons. Particulate matters (PMs) with different sizes, elements and dissolvable ions in PMs were analyzed. Pollutant concentrations, characteristics and seasonal variations were discussed in order to describe the pollution status and the possible sources in this region. Enriched factors of K, Ca, Cr, Fe, Cu, Zn, As, Cd and Pb were all higher than 10. Concentrations of dissolvable ions were in the order of NO3 –, SO4 2– >NH4 + >Cl – >Ca 2+, K +, Na + >Mg 2+, F – . NO3 –, SO4 2–, NH4 +, Cl – were the most important ion pollutants in the three cities which accounted for 90.3–92.3% of total 9 ion concentrations. Ion concentrations in the PMs were in the order of PM1 >PM1–2.5 >PM2.5–10 >PM10 >TSP. More than 50% of the dissolvable ions exist in PM1 and the percentage increases to 73.9–94.8% in PM2.5. Human activities should be the main sources of the metallic pollutants, among which coal combustion was identified as the primary one.